Physics Laboratory Management: A Novel Use of QR Code Tag on Physics Equipment Storage Cabinet - Mahmudah, Ifa Rifatul; Maulidah, Rifa'atul (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
The application of QR codes in laboratory management is an increase, but the study of its use in the physics laboratory equipment storage is rarely done. There are numerous in various laboratory equipment stored in the physics laboratory. Well-organized storage with QR-code installment in the cabinet should be a big consideration to assist laboratory users at trace and emplace the equipment in an appropriate. This study aims to develop the application of QR codes in designing the layout of laboratory equipment at the cabinet. The development of the storage layout of laboratory equipment refers to the research and development methods. There are two main focuses in this study, specifically are how to design the layout storage of laboratory equipment and how to develop the QR code scanning system in a physics laboratory. The questionnaire was distributed to 23 respondents, the highest result with 100% agreement shown when they assessed the utility of a QR code-based laboratory storage system and the design of a laboratory equipment layout. The laboratory users give a positive response to the laboratory management system that developed based on QR code. They consider the QR code system is an effective way of trace and emplace the laboratory equipment.